Maladministration as a Threat to the Rule of Law and Good Governance Principles in Public Service - Ardiana Ardiana (SALAM: Jurnal Sosial dan Budaya Syar-i, 2026)
Maladministration in public service delivery represents a fundamental challenge to governance quality in Indonesia, threatening both constitutional rule of law principles and internationally recognized good governance standards. This study examines the mechanisms through which maladministration undermines legal and governance frameworks, and analyzes the legal accountability systems available for addressing administrative misconduct. Employing normative juridical methodology with conceptual and statutory approaches, the research systematically examines primary legal materials including Law No. 37 of 2008 on the Ombudsman, Law No. 25 of 2009 on Public Service, and Law No. 30 of 2014 on Government Administration, complemented by secondary scholarly sources. The findings reveal that maladministration threatens rule of law principles through three primary mechanisms: displacement of legal supremacy by administrative discretion, erosion of equality before the law through discriminatory service provision, and weakening of separation of powers through ineffective oversight. Simultaneously, maladministration undermines good governance by creating accountability deficits, transparency gaps, rule of law failures, efficiency losses, and participation barriers. The legal framework provides administrative, civil, and criminal accountability pathways; however, implementation gaps persist, evidenced by only 64.7% compliance with Ombudsman recommendations. The study contributes to administrative law scholarship by providing integrated analysis of maladministration's dual threat to legal and governance systems, and by systematically mapping accountability mechanisms within the Indonesian legal context. Limitations include the normative methodology's inability to capture empirical dimensions of maladministration prevalence and institutional practice, suggesting future empirical and comparative research directions. Keywords: Maladministration, Rule Of Law, Good Governance, Public Service, Legal Accountability, Ombudsman, Administrative Law